Study on the influence mechanism of internet risks on the development risks of Chinese adolescents: the mediating role of digital dependence and the moderating role of digital skills - Lv, Shan; Hong, Yue; Huang, Yiyu (Frontiers in Psychology, 2025)
BackgroundFor the adolescent group who have grown up alongside the Internet, participating in digital life has become an important part of their daily practices. However, persistent negative online content exposure, interaction experiences and participation in online risky behaviors significant exacerbate adolescents’ developmental risks. This study examined how online content risks, interaction risks, and behavioral risks relate to adolescents’ developmental risks, and whether digital dependence mediates these effects and digital skills moderate them.MethodsThis cross-sectional study was conducted in 2025 among students from five schools in Y and H provinces, China, including one primary school, one junior high school, one senior high school, one junior college, and one university. 899 students (51.4% girls), aged 10–19 (Mage = 14.66, standard deviation [SD] = 2.78), participated.ResultsOnline content risks, interaction risks, and behavioral risks exert significant positive effects on the digital developmental risks of Chinese adolescents. Furthermore, digital dependence significantly mediated the effects of the three online risks on adolescents’ developmental risks related to alienation from reality. Finally, enhanced digital skills mitigated the positive effect of behavioral risks on digital developmental risks. In addition, the control variables of age, educational level, health status, and economic level were all significant predictors of digital developmental risks.ConclusionThe results suggest that adolescents’ developmental risks are closely linked to their online experiences, digital dependence, and digital skills. Targeted efforts to reduce harmful online exposure, curb excessive Internet reliance, and strengthen digital competencies may effectively mitigate risks of alienation from reality. Additionally, targeted monitoring and intervention efforts should prioritize those who are older adolescents, have lower educational attainment, are in poorer physical health, or come from economically disadvantaged households.